The Distribution of Academic Vocabulary List (AVL) in Undergraduate Theses: A Corpus Study - Fisma; Abidin Pammu; Ria Jubhari (Hasanuddin University, 2021)
This study is a corpus-based study that aims to find out the use of words in Gardner and Davies' (2014) Academic Vocabulary List (AVL) in Undergraduate Theses in the field of English Education. A 2.2 million-word called undergraduate theses corpus was created in this study. The corpus consists of 200 undergraduate theses compiled from 10 Universities in Indonesia. The result shows that AVL words account for 24.79% of the entire education undergraduate theses, which contained 557,658 running words. AVL contains 3,015 core academic words (lemmas). Based on word frequency criteria, this study found 573-word forms and 871 lemmas, which coverage 31.48% of the whole Gardner and Davies' AVL that occur at least 63 times in the entire corpus and the word has to occur at least five times in five universities. The finding shows that AVL is effective for the students in writing undergraduate theses. However some of the words that are closely related to the English Education field are not found in the AVL, therefore an attempt to develop a new academic vocabulary specific to the English Education field is needed.